1. The problem statement, all variables and given/known data From James Stewart's Essential Calculus Early Trancendentals, p.21 #5. Find an expression for a cubic function f if f(1)=6 and f(-1)=f(0)=f(2)=0 2. Relevant equations Used zeros of the function. 3. The attempt at a solution I understand that the values of x (assuming it's f(x)) which make the value 0 are the zeros of the function. We want these x values to make the whole statement 0, so since f(-1) = 0, then (x+1) is one of the zeros. Similarly (x-0) and (x-2) are zeros as well. If I put them together, I get (x+1)(x)(x-2), but then I don't know what to do with the f(1) = 6. The answer guide gives: f(x) = -3x(x+1)(x-2) For some reason, the (x-0) just dropped off, and somehow f(1)=6 equates to -3x, or maybe just -3, and the x is from the (x-0).